Low-flow anti-aging adhesive film for main-grid-free photovoltaic module and preparation method of low-flow anti-aging adhesive film
By using low flow and aging-resistant adhesive film in main gate photovoltaic modules, a dense silicon layer is formed through the combination and processing technology of EVA matrix resin and other materials, which solves the problem of the adhesive film being prone to aging and delamination, and improves the adhesive film and The adhesiveness and corrosion resistance of glass extend the life of the assembly and reduce power attenuation.
Patent Information
- Application Number
- CN202411531081.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
AI Technical Summary
The problem of the adhesive film used in main gate photovoltaic modules being prone to aging and delamination, affecting the stability and power performance of the module.
Using a low flow and aging resistance film, a dense silicon layer is formed by combining EVA matrix resin, crosslinking agent, aid crosslinking agent, silane coupling agent, functional additive, antioxidant, and anticorrosion additives to form a dense silicon layer to enhance the glue The adhesive force between the film and glass is cast and extruded by high-speed mixing and single-screw extruder, and then irradiated crosslinking to obtain a low flow and aging-resistant adhesive film.
It improves the aging adhesion between the adhesive film and glass, blocks external water vapor corrosion, enhances corrosion resistance, extends the service life of the components and reduces power attenuation.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic adhesive films, and in particular relates to a low-flow aging-resistant adhesive film for a main-grid-free photovoltaic module and a preparation method thereof. Background Art
[0002] With the development of technology, the main grid technology of solar cells has developed from MBB and SMBB to 0BB (no main grid). No main grid technology is a further upgrade of SMBB technology, and its cost reduction advantage is obvious. No main grid technology directly eliminates the main grid of the cell, further reducing silver consumption; in addition, copper welding strips are used to replace the original main grid to derive current in the component link. The diameter of the common welding strips of MBB components is 0.2-0.4mm, while the diameter of the 0BB welding strip is only 0.2mm, which has a smaller shading area and can increase the power of the component. At present, no main grid technology is widely used in TOPCon, XBC, HJT and other batteries.
[0003] The main busbar-free technologies currently include SmartWire, glue printing, laminating and welding glue dispensing. Among them, the glue printing solution has been mass-produced by leading photovoltaic companies and is the most widely used. The process of the glue solution is: first apply a glue dot body (UV glue, hot melt glue and other adhesives), solidify the entire solder strip on the battery cell using UV lamps, ovens and other equipment, and then achieve alloying of the solder strip and the battery cell through lamination. This solution is different from the welding glue dispensing solution in that it does not require welding, and can be fixed by glue dispensing or silk screen printing. The glue solution has simple equipment and strong stability, but there are problems such as shadows under the solder strip during EL testing and easy delamination and failure of the glue film under aging.
[0004] Therefore, how to overcome the defect that the adhesive film used in busbar-free photovoltaic modules is prone to aging and delamination is a technical problem that urgently needs to be solved in this field.
[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0006] The embodiments of the present disclosure at least provide a low-flow anti-aging adhesive film for busbar-free photovoltaic modules and a preparation method thereof.
[0007] In the first aspect, an embodiment of the present disclosure provides a low-flow aging-resistant adhesive film for a busbar-free photovoltaic module, which is prepared from raw materials including the following parts by weight: 80-100 parts by weight of EVA matrix resin, 0.2-1 parts by weight of a cross-linking agent, 0.4-1 parts by weight of a co-cross-linking agent, 0.1-0.5 parts by weight of a silane coupling agent, 0.05-0.3 parts by weight of a functional additive, 0.2-0.8 parts by weight of an antioxidant, and 0.05-0.3 parts by weight of an anti-corrosion additive; wherein the functional additive is a polyalkoxysilane, including multiple alkoxy groups and hydroxyl groups.
[0008] In an optional embodiment, the preparation method of the functional additive includes the following steps: step S1, adding γ-glycidyloxypropyltrimethoxysilane to a reactor, stirring at 500-1000r / min for 5-20min to obtain a pre-prepared solution; step S2, adding γ-aminopropyltriethoxysilane to the pre-prepared solution and reacting for 6-24h, stopping the reaction, and obtaining a reaction liquid; step S3, cooling the reaction liquid to room temperature to obtain the functional additive.
[0009] In an optional embodiment, in step S2, the molar ratio of γ-glycidyloxypropyltrimethoxysilane to γ-aminopropyltriethoxysilane is 2-2.5:1.
[0010] In an optional embodiment, the EVA matrix resin contains 20-33% by mass of vinyl acetate and has a melt flow rate of 4-15 g / 10 min.
[0011] In an optional embodiment, the cross-linking agent is any one or more combinations of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate and tert-butyl peroxy isopropyl formate.
[0012] In an optional embodiment, the auxiliary cross-linking agent is any one or more combinations of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate.
[0013] In an optional embodiment, the silane coupling agent is a combination of any one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxy tert-butyl silane, vinyl triacetoxy silane and vinyl tri(β-methoxyethoxy) silane.
[0014] In an optional embodiment, the antioxidant is any one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(4-nonylphenol) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris[2,4-di-tert-butylphenyl] phosphite and pentaerythritol dioctadecyl diphosphite.
[0015] In an optional embodiment, the anti-corrosion additive is any one or more combinations of magnesium hydroxide, magnesium oxide, calcium lactate, and zirconium phosphate.
[0016] In the second aspect, the embodiments of the present disclosure also provide a method for preparing a low-flow aging-resistant adhesive film for busbar-free photovoltaic modules as described above, comprising: mixing EVA matrix resin, cross-linking agent, auxiliary cross-linking agent, silane coupling agent, functional additives, antioxidants and anti-corrosion additives at high speed, extruding through a single-screw extruder, and then irradiating and cross-linking to obtain a low-flow aging-resistant adhesive film.
[0017] The beneficial effect of the present invention is that the functional additives of the low-flow aging-resistant adhesive film for busbar-free photovoltaic modules and the preparation method thereof contain multiple alkoxy groups and hydroxyl groups, which can form a dense silicon layer on the surface of the photovoltaic glass, cooperate with the adhesion between the silane coupling agent and the glass, block external water vapor erosion, and thus improve the aging adhesion between the film and the glass. In addition, the hydroxyl groups in the structure can also spontaneously condense into a polysiloxane chain structure, which can be coated with inorganic micro-nano anti-corrosion additives such as calcium lactate, increase the compatibility of the anti-corrosion additives with the film body, and further improve the aging resistance.
[0018] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and claims.
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below for detailed description as follows. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0022] In this document, as used herein, expressions such as "at least one of..." when following a list of elements modify the entire list of elements rather than modifying the individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0023] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0024] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0025] The embodiment of the present disclosure provides a low-flow anti-aging adhesive film for busbar-free photovoltaic modules, which is prepared from raw materials including the following parts by weight: 80-100 parts by weight of EVA matrix resin, 0.2-1 parts by weight of cross-linking agent, 0.4-1 parts by weight of auxiliary cross-linking agent, 0.1-0.5 parts by weight of silane coupling agent, 0.05-0.3 parts by weight of functional additive, 0.2-0.8 parts by weight of antioxidant and 0.05-0.3 parts by weight of anti-corrosion additive; wherein the functional additive is a polyalkoxysilane, including multiple alkoxy groups and hydroxyl groups.
[0026] In some embodiments, specifically, the preparation method of the functional additive includes the following steps: step S1, adding γ-glycidyloxypropyltrimethoxysilane into a reactor, stirring at 500-1000r / min for 5-20min to obtain a pre-prepared solution; step S2, adding γ-aminopropyltriethoxysilane to the pre-prepared solution and reacting for 6-24h, stopping the reaction, and obtaining a reaction liquid; step S3, cooling the reaction liquid to room temperature to obtain the functional additive.
[0027] In some embodiments, specifically, in step S2, the molar ratio of γ-glycidyloxypropyltrimethoxysilane to γ-aminopropyltriethoxysilane is 2.5:1.
[0028] In some embodiments, specifically, the EVA matrix resin contains 20-33% by mass of vinyl acetate, and has a melt flow rate of 4-15 g / 10 min.
[0029] In some embodiments, specifically, the cross-linking agent is any one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate and tert-butyl peroxy isopropyl formate.
[0030] In some embodiments, specifically, the auxiliary cross-linking agent is any one or more combinations of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate.
[0031] In some embodiments, specifically, the silane coupling agent is a combination of any one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxy tert-butyl silane, vinyl triacetoxy silane and vinyl tri(β-methoxyethoxy) silane.
[0032] In some embodiments, specifically, the antioxidant is any one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(4-nonylphenol) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris[2,4-di-tert-butylphenyl] phosphite and pentaerythritol dioctadecyl diphosphite.
[0033] In some embodiments, specifically, the anti-corrosion agent is any one or more combinations of magnesium hydroxide, magnesium oxide, calcium lactate, and zirconium phosphate.
[0034] The disclosed embodiments also provide a method for preparing a low-flow, aging-resistant adhesive film for busbar-free photovoltaic modules as described above, comprising: mixing EVA matrix resin, a cross-linking agent, a co-cross-linking agent, a silane coupling agent, a functional additive, an antioxidant and an anti-corrosion additive at high speed, extruding the mixture through a single-screw extruder, and then cross-linking by irradiation to obtain a low-flow, aging-resistant adhesive film.
[0035] Example 1
[0036] The preparation method of the low-flow aging-resistant adhesive film for busbar-free photovoltaic modules is as follows: 100 parts by weight of EVA with a melt flow rate of 15 g / 10 min, 0.5 parts by weight of tert-butyl peroxy-2-ethylhexyl carbonate, 0.4 parts by weight of triallyl isocyanurate, 0.1 parts by weight of vinyl triethoxysilane, 0.05 parts by weight of functional additives, 0.2 parts by weight of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.05 parts by weight of magnesium hydroxide are mixed at high speed, extruded by casting through a single-screw extruder, and then irradiated and cross-linked to obtain the low-flow aging-resistant adhesive film.
[0037] The preparation steps of the functional additive are:
[0038] (1) adding γ-glycidyloxypropyltrimethoxysilane into a reactor and stirring at 500 r / min for 5 min;
[0039] (2) adding γ-aminopropyltriethoxysilane to the above liquid, reacting for 6 hours, and stopping the reaction, wherein the molar ratio of γ-glycidyloxypropyltrimethoxysilane to γ-aminopropyltriethoxysilane is 2:1;
[0040] (3) Cooling the reaction solution to room temperature to obtain a functional additive.
[0041] Example 2
[0042] The preparation method of the low-flow aging-resistant adhesive film for busbar-free photovoltaic modules is as follows: 100 parts by weight of EVA with a melt flow rate of 6 g / 10 min, 0.6 parts by weight of tert-amyl peroxy (2-ethylhexyl) carbonate, 0.9 parts by weight of trimethylolpropane trimethacrylate, 0.3 parts by weight of vinyl trimethoxysilane, 0.2 parts by weight of functional additives, 0.4 parts by weight of tris(2,4-di-tert-butylphenyl) phosphite and 0.2 parts by weight of magnesium hydroxide are mixed at high speed, extruded by cast casting through a single-screw extruder, and then irradiated and cross-linked to obtain the low-flow aging-resistant adhesive film.
[0043] The preparation steps of the functional additive are:
[0044] (1) adding γ-glycidyloxypropyltrimethoxysilane into a reactor and stirring at 1000 r / min for 5 min;
[0045] (2) adding γ-aminopropyltriethoxysilane to the above liquid, reacting for 12 hours, and stopping the reaction, wherein the molar ratio of γ-glycidyloxypropyltrimethoxysilane to γ-aminopropyltriethoxysilane is 2:1;
[0046] (3) Cooling the reaction solution to room temperature to obtain a functional additive.
[0047] Example 3
[0048] The preparation method of the low-flow aging-resistant adhesive film for busbar-free photovoltaic modules is as follows: 80 parts by weight of EVA with a melt flow rate of 4 g / 10 min, 1 part by weight of tert-butyl peroxy-2-ethylhexyl carbonate, 0.4 parts by weight of trimethylolpropane trimethacrylate, 0.5 parts by weight of vinyl triacetoxysilane, 0.3 parts by weight of functional additives, tris(4-nonylphenol) phosphite and 0.3 parts by weight of calcium lactate are mixed at high speed, extruded by a single-screw extruder, and then irradiated and cross-linked to obtain the low-flow aging-resistant adhesive film.
[0049] The preparation steps of the functional additive are:
[0050] (1) adding γ-glycidyloxypropyltrimethoxysilane into a reactor and stirring at 500 r / min for 20 min;
[0051] (2) adding γ-aminopropyltriethoxysilane to the above liquid, reacting for 24 hours, and stopping the reaction, wherein the molar ratio of γ-glycidyloxypropyltrimethoxysilane to γ-aminopropyltriethoxysilane is 2:1;
[0052] (3) Cooling the reaction solution to room temperature to obtain a functional additive.
[0053] Example 4
[0054] The preparation method of the low-flow anti-aging adhesive film for busbar-free photovoltaic modules is the same as that of Example 2, except that the raw materials do not contain functional additives.
[0055] Example 5
[0056] The preparation method of the low-flow anti-aging adhesive film for busbar-free photovoltaic modules is the same as that in Example 2, except that the raw materials do not contain a silane coupling agent.
[0057] The assembly manufacturing process is as follows: first, arrange low-temperature welding wires on the cells, then lay low-weight adhesive film on the welding wires, heat at 80-120℃ for 3-30s to fix the welding wires on the cells, and finally cover with conventional adhesive film and glass, and laminate them into assemblies. Test the high-temperature and high-humidity aging performance (DH) of the assembly in accordance with GB / T 29848-2018, and observe whether there are welding wire slippage, bubbles, and other appearance defects around the welding strips.
[0058] Specifically, the performance of the components prepared in Examples 1-5 is shown in Table 1 below.
[0059] Table 1
[0060] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Initial adhesion to glass / N 146 158 144 128 45 Adhesion strength between DH1000 and glass / N 125 133 120 56 2 Initial appearance No change No change No change No change No change DH1000 Power Attenuation 1.42% 1.44% 1.46% 3.11% 6.32%
[0061] Specifically, it can be seen from Table 1 above that the initial glass bonding strength of Example 4 without adding functional additives is slightly lower than that of Examples 1-3 with added functional additives, and the glass bonding strength is greatly reduced after the DH1000 anti-aging test. This is because there are no alkoxy and hydroxyl groups in the functional additives to form a dense silicon layer on the surface of the photovoltaic glass, which leads to the entry of water vapor, accelerates aging, and causes power attenuation.
[0062] Specifically, in Example 5, without adding a silane coupling agent, the initial glass bonding force and the DH1000 glass bonding force are both extremely low. This is because the functional additive alone cannot play an anti-aging effect and must work synergistically with the silane coupling agent.
[0063] In summary, the functional additives of the low-flow aging-resistant adhesive film for busbar-free photovoltaic modules and the preparation method thereof contain multiple alkoxy groups and hydroxyl groups, which can form a dense silicon layer on the surface of the photovoltaic glass, cooperate with the adhesion between the silane coupling agent and the glass, block external water vapor erosion, and thus improve the aging adhesion between the film and the glass. In addition, the hydroxyl groups in the structure can also spontaneously condense into a polysiloxane chain structure, which can be coated with inorganic micro-nano anti-corrosion additives such as calcium lactate, increase the compatibility of the anti-corrosion additives with the film body, and further improve the aging resistance.
[0064] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A low-flow anti-aging adhesive film for busbar-free photovoltaic modules, characterized in that: Prepared from the following raw materials in parts by weight: 80-100 parts by weight of EVA matrix resin, 0.2-1 parts by weight of crosslinking agent, 0.4-1 parts by weight of auxiliary crosslinking agent, 0.1-0.5 parts by weight of silane coupling agent, 0.05-0.3 parts by weight of functional additive, 0.2-0.8 parts by weight of antioxidant and 0.05-0.3 parts by weight of anti-corrosion additive; wherein The functional auxiliary agent is polyalkoxysilane, which includes multiple alkoxy groups and hydroxyl groups.
2. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: Step S1, adding γ-glycidyloxypropyltrimethoxysilane into a reactor, stirring at 500-1000 r / min for 5-20 min to obtain a pre-prepared solution; Step S2, adding γ-aminopropyltriethoxysilane to the pre-prepared solution and reacting for 6-24 hours, stopping the reaction to obtain a reaction solution; Step S3, cooling the reaction solution to room temperature to obtain a functional additive.
3. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 2, characterized in that: In the step S2, the molar ratio of γ-glycidyloxypropyltrimethoxysilane to γ-aminopropyltriethoxysilane is 2-2.5:
1.
4. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The EVA matrix resin contains 20-33% by mass of vinyl acetate and has a melt flow rate of 4-15 g / 10 min.
5. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The cross-linking agent is any one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate and tert-butyl peroxy isopropyl formate.
6. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The auxiliary cross-linking agent is any one or more combinations of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate and pentaerythritol triacrylate.
7. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The silane coupling agent is any one or more combinations of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxy tert-butyl silane, vinyl triacetoxy silane and vinyl tri(β-methoxyethoxy) silane.
8. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The antioxidant is any one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(4-nonylphenol) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris[2,4-di-tert-butylphenyl] phosphite and pentaerythritol dioctadecyl diphosphite.
9. The low-flow anti-aging adhesive film for busbar-free photovoltaic modules according to claim 1, characterized in that: The anti-corrosion additive is any one or more combinations of magnesium hydroxide, magnesium oxide, calcium lactate and zirconium phosphate.
10. A method for preparing a low-flow anti-aging adhesive film for a busbar-free photovoltaic module according to any one of claims 1 to 9, characterized in that: include: The EVA matrix resin, crosslinking agent, auxiliary crosslinking agent, silane coupling agent, functional additive, antioxidant and anti-corrosion additive are mixed at high speed, extruded by casting through a single screw extruder, and then irradiated and crosslinked to obtain a low-flow aging-resistant adhesive film.
